Trends and Determinants of The Maternal Mortality Ratio Based on Healthcare Resources - Eka Nur Sejati; Elsye Maria Rosa; Bayu Anggileo Pramesona (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
ABSTRACT Health resources play an essential role in realizing the unattainable Sustainable Development Goals targets in lowering maternal mortality ratio (MMR) globally. The study aimed to analyze trends and determinants of MMR based on the number of healthcare resources in Indonesia. This study was a descriptive retrospective study with a cross-sectional approach. Data on the health program achievements in Central Java province, Indonesia from 2016 to 2020 was analyzed using bivariate analysis with scatter plots, statistical analysis with Pearson correlation tests, and multiple linear analysis using Tableau software. Results showed that the MMR was decreased in 2016-2019, however it was increased in 2020. The ratio of obstetrics-gynecology specialists and nutritional personnel had impact on the maternal mortality ratio in 2016 (p-value <0.05). While the general practitioners and nutritional workers ratio also affected the maternal mortality ratio in 2017 and 2019 to 2020 with p-value <0.05. Our study concluded that the trend of MMR in Indonesia was affected by the number of healthcare personnel resources. It is recommended that the Indonesian government should fulfill the quantity and equalization of the distribution of healthcare personnel resources particularly the obstetrics-gynecology specialists, general practitioners, and nutritional workers so the MMR could be decreased.